Phenolic compound profiles and antioxidant capacity of persea americana mill. peels and seeds of two varieties - Kosinska, A.; Karamac, M.; Estrella, I.; Hernández, T.; Bartolomé, B.; Dykes, Gary (2012)
Avocado processing by the food and cosmetic industries yields a considerable amount of phenolic-rich byproduct such as peels and seeds. Utilization of these byproducts would be favorable from an economic point of view. Methanolic (80%) extracts obtained from lyophilized ground peels and seeds of avocado (Persea americana Mill.) of the Hass and Shepard varieties were characterized for their phenolic compound profiles using the HPLC-PAD technique. The structures of the identified compounds were subsequently unambiguously confirmed by ESI-MS. Compositional analysis revealed that the extracts contained four polyphenolic classes: flavanol monomers, proanthocyanidins, hydroxycinnamic acids, and flavonol glycosides. The presence of 3-O-caffeoylquinic acid, 3-O-p-coumaroylquinic acid, and procyanidin A trimers was identified in seeds of both varieties. Intervarietal differences were apparent in the phenolic compound profiles of peels. Peels of the Shepard variety were devoid of (+)-catechin and procyanidin dimers, which were present in the peels of the Hass variety. Peels of both varieties contained 5-O-caffeoylquinic acid and quercetin derivatives. The differences in the phenolic profiles between varietals were also apparent in the different antioxidant activity of the extracts. The peel extracts had a higher total phenolic compound content and antioxidant activity when compared to the seed extracts. The highest TEAC and ORAC values were apparent in peels of the Haas variety in which they amounted to 0.16 and 0.47 mmol Trolox/g DW, respectively. No significant (p > 0.05) differences were apparent between the TEAC values of seeds of the two varieties but the ORAC values differed significantly (p < 0.05). Overall these findings indicate that both the seeds and peel of avocado can be utilized as a functional food ingredient or as an antioxidant additive. © 2012 American Chemical Society.